PENGEMBANGAN POTENSI WISATA JAKARTA HIDDEN TOUR DI KELURAHAN PENJARINGAN KOTAMADYA JAKARTA UTARA. - Cempaka (PANDITA : Interdisciplinary Journal of Public Affairs, 2021)
The development of the concept of tourism in Indonesia is one type of industry that increases marketing and opens up jobs so that it has an impact on national income. The increase in tourists is a factor in increasing Indonesia's foreign exchange income, so that it affects the welfare of the community in overcoming poverty. Tourism development can provide opportunities for community economic activities to move. Based on Law Number 10 of 2009 CHAPTER VII Article 26 points (a) to (l) it explains that travel entrepreneurs have obligations that must be implemented. This also applies to the Jakarta Hidden Tour, which is one of the tourist travel businesses that make slum areas a tourist attraction. This study uses the theory of Tourism policy and community participation. This study uses qualitative research methods using interview data collection techniques, observation and documentation. The results of this study conclude that the Jakarta Hidden Tour has implemented Law Number 10 of 2009 CHAPTER VII Article 26 point (a) which is about security, however the Jakarta Hidden Tour violates point (m) which is about the obligation to maintain the image of the country.